2000
DOI: 10.2500/108854100778248287
|View full text |Cite
|
Sign up to set email alerts
|

Possible Mechanisms of Late-Life-Onset Allergic Diseases and Asthma in the Senior Citizen

Abstract: The clinical spectrum of allergic diseases and asthma changes over the life span of the individual and is influenced by a wide variety of anatomic, physiologic, and immunologic factors. Nowhere do these changes play a more important role than in the elderly patient with allergic disease or asthma where the culmination of these events contribute to disease expression, which at times can result in irreversible endstage disease. It is estimated that between 2010 and 2030 the elderly population will increase by 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…This may be due to concomitant age-related changes in nasal physiology in the elderly (nasal glandular atrophy, vascular changes, decreased nasal humidification, decreased mucociliary clearance, and structural changes of the nose) (7,8,10,23), which may contribute to more frequent rhinorrhea. In fact, it is likely that several mechanisms underlie the pathogenesis of rhinitis in the elderly, with potential interaction between inflammatory conditions and the influence of aging on nasal physiology (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to concomitant age-related changes in nasal physiology in the elderly (nasal glandular atrophy, vascular changes, decreased nasal humidification, decreased mucociliary clearance, and structural changes of the nose) (7,8,10,23), which may contribute to more frequent rhinorrhea. In fact, it is likely that several mechanisms underlie the pathogenesis of rhinitis in the elderly, with potential interaction between inflammatory conditions and the influence of aging on nasal physiology (24).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in life expectancy goes in parallel with a concern for better quality of life. Studies on allergic and respiratory diseases in geriatric populations have shown that allergens, infections, and irritants can be important triggers of inflammation, regardless of age-related physiologic changes in the immune system, connective tissue, and vasculature that may predispose for chronic rhinitis (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…In fact, although in their daily work allergists see more and more elderly patients with rhinitis, asthma and other allergic diseases, few studies have assessed the prevalence of atopy and allergic diseases in elderly patients with objective measures such as skin prick tests to aeroallergens or food allergens or serum IgE determination [2,3,4,5,6]. Because of changing world demographics, it is estimated that the elderly population will increase by 75% between 2010 and 2030 [7]. …”
Section: Introductionmentioning
confidence: 99%
“…These include thymic involution, which may impact immune tolerance, decreased T-cell function and decreased T-cell response to growth factors [26]. Hum oral immune responses also change with age.…”
Section: Allergic Rhinitismentioning
confidence: 99%